O fortalecimento do assoalho pélvico e a prevenção da incontinência urinária no climatério: uma revisão integrativa - Souza, Keity Miranda de (Brasil, 2025)
This integrative review aimed to investigate the evidence available in the literature on the contribution of strengthening the pelvic floor in preventing urinary incontinence during menopause. The review was carried out in the Web Of Science, EMBASE and MEDLINE databases through the Virtual Health Library, indexed from 2018 to 2023. Four articles were included in the review that provided evidence demonstrating that pelvic floor strengthening techniques are efficient strategies for maintaining muscle strength by reducing the symptoms of urinary incontinence in climacteric women. In addition to treating the already established disease, strengthening the pelvic muscles is also effective in preventing the emergence of UI symptoms. Among the benefits of the intervention, its low cost and less invasive techniques stand out.